1999
DOI: 10.1063/1.371048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of amorphous CNx thin films by pulsed laser deposition using a radio frequency radical beam source

Abstract: Articles you may be interested inPreparation of α -Al 2 O 3 thin films by electron cyclotron resonance plasma-assisted pulsed laser deposition and heat annealing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 40 publications
(34 reference statements)
0
24
1
Order By: Relevance
“…Broad absorption band 2 at 1000-1700 cm À1 indicates that the films structure is predominantly amorphous with sp 2 -C vibration modes, and is related to Raman active disordered (D band) and graphite-like (G band) modes [30,31]. Band 3 at 1100-1400 cm À1 , band 4 at 1500-1700 cm À1 and band 5 at around 2200 cm À1 are due to C-N, C@C and/or C@N and C"N stretching vibration modes, respectively [9,32,33]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad absorption band 2 at 1000-1700 cm À1 indicates that the films structure is predominantly amorphous with sp 2 -C vibration modes, and is related to Raman active disordered (D band) and graphite-like (G band) modes [30,31]. Band 3 at 1100-1400 cm À1 , band 4 at 1500-1700 cm À1 and band 5 at around 2200 cm À1 are due to C-N, C@C and/or C@N and C"N stretching vibration modes, respectively [9,32,33]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While claims of crystallinity remain unresolved, there have been interesting results on the physical properties of amorphous CN (a-CN x ) films [8]. The a-CN x films is expected to be an interesting new material because it exhibits outstanding properties, such as high value of hardness, low friction, chemical inertness, and variable electrical conductivity and optical band gap [9]. The local structural property that distinguishes potentially superhard and dense C 3 N 4 structures from low-density and softer material is a carbon coordination, which hard materials require sp 3 -C in the C 3 N 4 network, while sp 2 -C will leads much softer materials [10].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to synthesis amorphous carbon nitride is much higher [2,3,4]. Amorphous carbon nitride (a-CN x ) has many interesting properties such as extreme hardness, low friction coefficient, and variable optical band gap [5]. The presence of hydrogen commonly found in carbon nitride films is the reason why carbon nitride tends to form as amorphous films.…”
Section: Introductionmentioning
confidence: 99%
“…Among the above mentioned techniques, the PLD is a promising way to deposit carbon nitride films with enhanced physical, chemical and electrochemical properties because it can be easily carried out even on non-conductive substrates and at low substrate temperatures during film growth. Up to now, most of the works deal with the deposition of a-C:N films by nanosecond pulsed laser deposition [12,21,22]. Recent studies have shown the ability to dope amorphous carbon (a-C) materials by femtosecond pulsed laser deposition (fs-PLD) [18,23] but nitrogen doped a-C films deposited by femtosecond PLD, in particular with plasma assistance, is still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%